Disrupted calcium dynamics and electrophysiological activity in the stratum pyramidale and hippocampal alveus during fear conditioning in the 5xFAD model of Alzheimer’s disease - Erofeev, Alexander; Vinokurov, Egor; Bol’shakova, Anastasia; Bezprozvanny, Ilya; Vlasova, Olga (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) is a neurodegenerative disorder that leads to progressive cognitive decline and significant disruptions in hippocampal neural networks, critically impacting memory and learning. Understanding the neural mechanisms underlying these impairments is essential for developing effective therapies. The 5xFAD mouse model, known for progressive neurodegeneration and cognitive deficits, provides a valuable platform for investigating associative learning and memory impairments related to AD. However, the in vivo electrophysiological state of the hippocampal alveus in 5xFAD mice during learning and memory formation remains poorly understood. Here, we performed in vivo one-photon calcium imaging of CA1 hippocampal neurons with wireless electrophysiological recordings from the hippocampal alveus in freely moving 5xFAD mice to explore specific neural alterations during a fear conditioning test. Our results demonstrate significant deficits in the learning and memory capacities of 5xFAD mice, showing impairments in hippocampal-dependent contextual and tone-associated memory retrieval, along with disrupted calcium dynamics and impaired electrophysiological activity in the hippocampal alveus. These findings reveal patterns of network dysregulation associated with AD. These findings enhance our understanding of the specific neural dysfunctions contributing to the cognitive decline associated with memory loss in AD and emphasize the value of applying in vivo methods to elucidate neurodegenerative mechanisms. This approach provides a foundation for future studies on AD pathophysiology and may inform the development of targeted therapeutic strategies to mitigate memory impairments in AD.